Are (poly)phenols contained in 100% fruit juices mediating their effects on cardiometabolic risk factors? A meta-regression analysis - Micek, Agnieszka; Currenti, Walter; Mignogna, Cristiana; Rosi, Alice; Barbagallo, Ignazio; Alshatwi, Ali A.; Del Rio, Daniele; Mena, Pedro; Godos, Justyna (Frontiers in Nutrition, 2023)
The consumption of 100% fruit juices has not been associated with substantial detrimental outcomes in population studies and may even contribute to improving the cardiometabolic profile if included in a healthy balanced diet. The main contributors to such potential beneficial effects include vitamins, minerals, and likely the (poly)phenol content. This study aimed to investigate whether the (poly)phenols contained in 100% fruit juices may mediate their effects on cardiometabolic risk factors based on published randomized controlled trials (RCT). A systematic search in PubMed/MEDLINE and Embase, updated till the end of October 2022, was carried out to identify RCT providing quantitative data on (poly)phenol content in 100% fruit juices and used as an intervention to improve cardiometabolic parameters such as blood lipids, glucose, and blood pressure. Meta-regression analysis was performed to calculate the effect of the intervention [expressed as standardized mean difference and 95% confidence intervals (CI)] using the (poly)phenol content as moderator. A total of 39 articles on RCT investigating the effects of 100% fruit juices on cardiometabolic risk factors reporting data on total (poly)phenol and anthocyanin content were included in the analysis. Total (poly)phenol content was substantially unrelated to any outcome investigated. In contrast, each 100 mg per day increase in anthocyanins was related to 1.53 mg/dL decrease in total cholesterol (95% CI: -2.83, -0.22, p = 0.022) and 1.94 mg/dL decrease in LDL cholesterol (95% CI: -3.46, -0.42, p = 0.012). No other potential mediating effects of anthocyanins on blood triglycerides, glucose, systolic and diastolic pressure were found, while a lowering effect on HDL cholesterol after excluding one outlier study was observed. In conclusion, the present study showed that anthocyanins may mediate the potential beneficial effects of some 100% fruit juices on some blood lipids. Increasing the content of anthocyanins through specific fruit varieties or plant breeding could enhance the health benefits of 100% fruit juices.